IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LISTEN–READ–DISCUSS (LRD) STRATEGY AT MA NURUSSABAH PRAYA TENGAH - Terasne, Terasne; Sugianto, Nanang; Wahab, Abdul; Ulfa, Maria (IKIP Mataram, 2018)
This research was aimed at describe whether listen-read-discuss (LRD) strategy be able to improve students’ reading comprehension or not. It was a classroom action research. The data collected uses quantitative and qualitative data. Quantitative data was gained from the result of pre-test and post-test from reading test. Meanwhile, qualitative data was gained from the result of observation sheets toward students and teachers activity. The instrument uses were test and observation sheet. The result shows that the strategy be able to improve the students’ reading comprehension in report text. The improvement can be seen from the mean score of students from pre-test, post-test one, and post-test two. The mean score of pre-test was 69.5 (35%), there were seven students who passed the minimum passing grade, in the post-test one, 72.2 (60%), twelve students passed the minimum passing grade and in the post-test two, 78.25 (85%), seventeen students passed the minimum passing grade (KKM).